PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN AKTIVITAS DAN PRESTASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN KESETIMBANGAN KIMIA KELAS XI IPA SMA IT-AL-FITYAH - Anita, Sri; Holiwarni, Betty; Herdini, Herdini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2025)
Abstract: The learning activeness of students in class XI Science SMA IT AlFityah is low, low activeness causes low learning achievement of students. This research aims to determine the application of the Discovery Learning learning model to students in class XI Science at SMA IT Al-Fityah which aims to improve and find solutions to real problems in improving students' learning achievements. This research has cycles, each cycle consists of 4 stages of activities that are interrelated and continuous, namely; planning, implementation (acting), observation (observing), and reflection (reflecting). The research results of the discovery learning model show that students' learning completeness before action and after action is; cycle I (70.37%), and cycle II (92.59%). Thus, it can be concluded that there is a significant change in increasing learning outcomes between before and after being given classroom action by applying the discovery learning learning model to students in class XI Science at SMA IT Al-Fityah so that this research is considered to have been successful. Key Words: Activities, Learning Achievement, Discovery Learning, Quality of Education.